The Caldwell & Moloy Classification of Female pelvic shape: Still Relevant after 80 years? - Kuliukas, Lesley; Kuliukas, Algis; Franklin, Daniel; Flavel, Ambika (2018)
The Caldwell-Moloy (1933) classification of four groups of female pelvic shape, Gynaecoid, Anthropoid, Android and Platypelloid, has been traditionally taught to students of midwifery and medicine and is still reported in the most recent midwifery and gynaecological textbooks. For decades, midwifery students have been instructed that knowing a woman’s pelvic shape would help evaluate possible disruptions to the normal progress of labour. However, the use of these classifications was always dubious, as it was difficult, if not impossible to categorise a woman into her pelvic “type” by her body shape. Using modern pelvimetric methodologies and geometric morphometric (GM) analysis techniques, on an albeit small sample, we found that the real morphometric variation present in the female human pelvis does not reflect the classification. GM analysis was carried out on sets of pelvic landmarks from scans of women living in Western Australia. 64 anonymous female multi-detector computer tomography (MDCT) scans were used for most of the study and 51 male scans were also examined for comparison. Principle component analysis (PCA) found that there was no obvious clustering into the four distinct types of pelvis in the Caldwell-Moloy classification, but rather an amorphous, cloudy continuum of shape variation. Until more data is collected to confirm or deny the statistical significance of this shape variation, it is recommended that teachers and authors of midwifery, obstetrics and gynaecological texts be more cautious about continuing to promote the Caldwell-Moloy classification, as our results show no support for the long taught ‘four types’ of pelvis.